2022
DOI: 10.1016/j.cub.2021.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Massive genome inversion drives coexistence of divergent morphs in common quails

Abstract: Highlights d A chromosomal inversion of 115 Mbp, 12% of the genome, is found in common quails d Birds with the inversion are darker, heavier, and have rounder wings d These birds do not undertake the characteristic longdistance migration d The sequence in the inversion is highly divergent and originated before speciation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 67 publications
2
39
0
Order By: Relevance
“…One hundred years after Alfred Sturtevant first provided evidence of chromosomal inversions in laboratory stocks of Drosophila (29) and, separately, forest-prairie ecotypes were first described in wild populations of Peromyscus (7), we found that a large chromosomal inversion is key to ecotype divergence in this classic system. Inversions have been identified in association with divergent ecotypes in diverse species, including plants (30)(31)(32)(33), invertebrates (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), fish (46,47), and birds (48)(49)(50)(51)(52). In mammals, however, evidence for ecotype-defining inversions is limited [( 53), but see (54)].…”
Section: Discussionmentioning
confidence: 99%
“…One hundred years after Alfred Sturtevant first provided evidence of chromosomal inversions in laboratory stocks of Drosophila (29) and, separately, forest-prairie ecotypes were first described in wild populations of Peromyscus (7), we found that a large chromosomal inversion is key to ecotype divergence in this classic system. Inversions have been identified in association with divergent ecotypes in diverse species, including plants (30)(31)(32)(33), invertebrates (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), fish (46,47), and birds (48)(49)(50)(51)(52). In mammals, however, evidence for ecotype-defining inversions is limited [( 53), but see (54)].…”
Section: Discussionmentioning
confidence: 99%
“…In that respect, it is interesting that many supergenes affect behaviour. For example, a supergene regulates male mating behaviour in the ruff [13], and supergenes regulate migration behaviour in the common quail and in rainbow trout [17,127]. Variation in behaviour allows individuals to select their environment, thereby increasing environmental predictability and providing conditions under which supergene evolution is favourable.…”
Section: Discussionmentioning
confidence: 99%
“…The best-known examples are sex chromosomes [6,7,11]. Others underpin alternative behaviour syndromes and plumage morphs in birds [12][13][14][15][16][17][18], mimetic colour morphs in butterflies [19,20], self-incompatibility in plants [21][22][23], mating types in fungi [24] and segregation distortion in various taxa [25,26]. Five supergenes have been recently discovered in ants (more than in any other animal family), and they all regulate the number of reproductive queens contained within a colony-a key aspect of the social organization of social insect colonies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome-scale studies have illuminated wide-ranging impacts of supergene evolution on complex phenotypes across diverse taxa (e.g. Schwander et al, 2014 ; Pearse et al, 2019 ; Hager et al, 2022 ; Joron et al, 2011 ; Kunte et al, 2014 ; Kess et al, 2019 ; Lundberg et al, 2017 ; Roberts et al, 2009 ; Sanchez-Donoso et al, 2022 ; Funk et al, 2021 ). Currently, the mechanisms by which functionally divergent supergene haplotypes evolve in the face of multiple evolutionary forces remain poorly understood, presenting a critical gap in knowledge.…”
Section: Introductionmentioning
confidence: 99%